Moving Vehicle Recognition and Feature Extraction From Tunnel Monitoring Videos - Aiyan Lu; Luo Zhong; Lin Li; Qingbo Wang (Institute of Advanced Engineering and Science, 2013)
In recent decades, many government agencies and famous universities are researching the intelligent traffic video monitoring system. According to the tunnel monitoring video, this paper uses the combination of background subtraction method and three frame differencing method for moving vehicle detection , and designs the geometric parameters and combined parameters for vehicle classification, finally makes up a vehicle classifier, based on these characteristics parameters. DOI: http://dx.doi.org/10.11591/telkomnika.v11i10.3465